Sss-class revival hunter. 02 - Sinnoa; Neida (Ize Press, 2025)
"His revenge complete, Gongja is finally ready to take on the Tower! Not only is he unkillable, but he keeps racking up skills with each death by monster. Add in the Blade Emperor’s guidance and he quickly reaches the tenth floor, which has yet to be conquered in this timeline—the perfect test to check how much stronger he is now. Will Gongja successfully become the first person to conquer the tenth floor and rewrite history?"--